Breakage of Needle during Intracavernosal Injection and Use of Portable Ultrasound Guidance for Removal - Wayland Hsiao; Fei Lian; Brooks Goodgame; Chad W. M. Ritenour; Jordan Angell; Viraj A. Master (Case Reports in Urology)
Purpose. Intracavernosal self-injection (ICI) was first described in 1982, and remains a viable therapy for erectile dysfunction. However, intracorporal needle breakage can be a rare complication of therapy. We report a rare complication of intracorporal needle breakage and a retention of a 30-gauge needle in a 42-year-old paraplegic man. We discuss our experience in using portable high-frequency ultrasound intraoperatively to visualize and guide removal of a retained ICI needle. Materials and Methods. Review of case and ultrasound technique are presented. Results. Using intraoperative ultrasound imaging, the retained intracorporal needle was successfully removed from the patient's penis without any complications. Follow-up ultrasonography and X-ray confirmed complete removal of the needle. Conclusions. We report on the successful implementation and use of a portable high-frequency ultrasound probe to visualize a retained intracorporal needle inside the penis and its use to guide removal. Given the rapid proliferation of portable ultrasound machines in the operating room and out in the field, we expect these imaging techniques to become routine, especially in urological emergencies.